Pengaruh Penggunaan Media Audio Visual dan Motivasi Terhadap Kemampuan Menganalisis Siswa Kelas VII Mts N Sungai Beremas Kecamatan Koto Balingka Kabupaten Pasaman Barat - Eldipama Kesambamula (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2019)
Abstract This study aims to describe: (1) the difference between the ability to analyze students taught through audio visual media and students taught with conventional VII grade MTsN Sungai Beremas models, (2) the difference between analyzing abilities of students who have high learning motivation who are taught using media audio visual with students who have high learning motivation students who are taught using the conventional VII grade MTsN Sungai Beremas model, (3) the difference between the ability to analyze students who have low learning motivation who are taught to use audio visual media with students who have low learning motivation conventional class VII MTsN Sungai Beremas, (4) interaction between the use of audio-visual media and learning motivation towards the ability to analyze class VII MTsN Sungai Beremas. The theories used are Nurgiyantoro (2010) and Priyatni (2013), Arsyad (2015), and Kompri (2015). This research is quantitative research, the method used is experiment. The study design was a 2x2 factorial anava design. The study population was all seventh grade students, totaling 47 people. The sampling technique uses simple random sampling, namely class VIIA as the experimental class and class VIIB control class. The data analysis technique used the t test and anava using the SPSS version 18 program. The results of the study show the following. (1) There is a significant difference between the ability to analyze students taught through audio visual media and students taught through conventional models, namely tcount> ttable (5,685 > 2,021). (2) There is a significant difference between the ability to analyze students who have high learning motivation who are taught to use audio visual media and students who have high learning motivation who are taught using conventional models, namely tcount> ttable (3,559 > 2,074). (3) There is a significant difference between the ability to analyze students who have low learning motivation who are taught to use audio-visual media with students who have low learning motivation taught by using conventional models namely tcount> ttable (4,796 > 2,080). (4) There is no interaction between audio visual media and learning motivation towards the ability to analyze the short story structure, namely Fcount <Ftable (0,001 < 4,06). Thus, there is the influence of the use of audio-visual media and motivation on the analytical ability of class VII students of MTsN Sungai Beremas, Koto Balingka District, West Pasaman Regency. Keywords: Listening, analyzing ability, motivation, audio visual media